2017
DOI: 10.1089/ten.tec.2017.0217
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Arteriovenous Shunts as a Method for Evaluating Tissue-Engineered Vascular Grafts in Large Animal Models

Abstract: There remains a need for large animal models to evaluate tissue-engineered vascular grafts (TEVGs) under arterial pressure to provide preclinical data for future potential human clinical trials. We present a comprehensive method for the interrogation of TEVGs, using an ovine bilateral arteriovenous (AV) shunt implantation model. Our results demonstrate that this method can be performed safely without complications, specifically acute heart failure, steal syndrome, and hypoxic brain injury, and it is a viable e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…S1). Exclusion of duplicates and then systematic screening of title and abstract using the Covidence platform revealed 321 studies, which was finally limited by thorough text reading to 68 studies based on inclusion criteria . These studies represented a total of 873 grafts: 258 occluded and 615 patent grafts at the end of the evaluation period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1). Exclusion of duplicates and then systematic screening of title and abstract using the Covidence platform revealed 321 studies, which was finally limited by thorough text reading to 68 studies based on inclusion criteria . These studies represented a total of 873 grafts: 258 occluded and 615 patent grafts at the end of the evaluation period.…”
Section: Resultsmentioning
confidence: 99%
“…Most grafts, however, were evaluated in the time frame 1 day to 6 months (736 grafts). The median TEVG patency was 83% (n = 873) for a median follow-up time of 56 days (95% confidence interval: [42,60]).…”
Section: Included Studies and Study Characteristicsmentioning
confidence: 99%
“…Electrospinning microfabrication technique is often used to generate tubular structures composed of nanofibers from different polymers. Composite scaffolds made of PCL/poly(ethylene oxide) (Wang et al, 2016 ) and PCL/PLGA (Ong et al, 2017 ) have been tested in animal models with the later acellular graft having been evaluated in an ovine bilateral arteriovenous shunt model. Such a model showed good results in term of patency (66%) and endothelialization of the lumen after 4 weeks of implantation, but the graft eventually dilated as a consequence of inadequate elastin content (Ong et al, 2017 ).…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…Notwithstanding that a direct comparison with commercially available arteriovenous grafts was not performed in this study, our finding is particularly significant considering that traditional 6 mm-diameter ePTFE grafts used as hemodialysis vascular accesses typically fail due to aggressive formation of intimal hyperplasia, and consequent stenosis with patency loss, at the venous anastomosis. [13,17] To address this critical aspect of arteriovenous shunting, several animal models have been developed over the last thirty years, [14,15] confirming that the primary unassisted patency of standard (5-6 mm in diameter) ePTFE grafts does not exceed 25% at 12 weeks in sheep [12,19] whereas secondary patency is approximately 67%. [20] In our study, deposition of endoluminal matrix of fibrotic and thrombotic origin was observed from day 30 to the end of the study along the graft length ( Figure 6; Figure S3, Supporting Information); however, this phenomenon, more accentuated close to the anastomoses (G1, G4, V2) than in the mid-graft region (G2-G3), did not result in a significant endoluminal stenosiswhose values stabilized at 25.06 ± 11.61% in V2 at 90 days-nor in a functional impairment, as confirmed by manual and ultrasound evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…To address this critical aspect of arteriovenous shunting, several animal models have been developed over the last thirty years, [ 14,15 ] confirming that the primary unassisted patency of standard (5–6 mm in diameter) ePTFE grafts does not exceed 25% at 12 weeks in sheep [ 12,19 ] whereas secondary patency is approximately 67%. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%